How Do Comprehensive Geriatric Assessment Approaches Impact Functional Status And Quality Of Life For Older Adults With Multiple Geriatric Syndromes? - Dodi Novriadi; Yudhi Hajianto Nugroho; Mutia Juliana (International Medical Journal Corp. Ltd, 2025)
Introduction: The global aging population has led to an increased prevalence of multiple geriatric syndromes such as frailty, multimorbidity, cognitive impairment, and functional decline. Comprehensive Geriatric Assessment (CGA) is a multidimensional, multidisciplinary diagnostic process designed to evaluate medical, psychological, and functional capabilities of older adults to develop coordinated treatment and follow-up plans. CGA aims to improve functional status, quality of life (QoL), and reduce adverse outcomes like falls and hospital readmissions. Methods: This systematic review analyzed studies involving older adults aged 65 years and above, focusing on CGA interventions compared to standard care. Data were extracted from randomized controlled trials and observational studies conducted in various healthcare settings including hospitals, community, and ambulatory units. Functional status and QoL outcomes were assessed using validated tools such as the Short Physical Performance Battery (SPPB) and EQ-5D. Results: CGA interventions demonstrated significant improvements in physical function, with SPPB scores increasing by up to 3.18 points at six months post-intervention. Quality of life measures also showed positive changes in both physical and mental health domains. Secondary outcomes included reductions in falls, frailty scores, and improvements in nutritional status and depressive symptoms. Discussion: The evidence supports CGA as an effective approach to managing complex health needs in older adults. Despite resource requirements, CGA offers long-term benefits by enhancing functional independence and overall well-being. Integration of tele-rehabilitation and digital monitoring may further improve accessibility and efficiency. Conclusion: Comprehensive Geriatric Assessment significantly improves functional status and quality of life in elderly populations. Continued efforts to standardize CGA protocols and train multidisciplinary teams are essential to maximize its global impact.